Asymmetric construction of substituted pyrrolidines via 1,3-dipolar cycloaddition of azomethine ylides and chiral acrylates derived from biomass - Llompart, David Fernando (2014)
The first application of chiral auxiliaries synthesized from levoglucosenone (a biomass-derived anhydrosugar) in asymmetric 1,3-dipolar cycloaddition reactions of azomethine ylides is herein reported. The corresponding pyrrolidinic cores were obtained in excellent levels of regio and stereocontrol, good to excellent π-facial selectivities, and could be isolated enantiomerically pure by column chromatography. Unexpected NMR observations coupled with DFT calculations allowed the stereochemical assignment of the synthesized adducts. The stereochemical assignment performed in silico was further unambiguously validated by structural X-ray diffraction analysis.